The alterations of carrier separation in kesterite solar cells. (October 2018) - Yang, Kee-Jeong; Kim, Sammi; Sim, Jun-Hyoung; Son, Dae-Ho; Kim, Dae-Hwan; Kim, Juran; Jo, William; Yoo, Hyesun; Kim, JunHo; Kang, Jin-Kyu
Abstract: Cu2 ZnSn(S, Se)S4 (CZTSSe) thin films have attracted attention as low-cost absorber materials for solar cells; however, further studies are required to develop flexible solar cells from this material and to achieve a high power conversion efficiency. Toward this objective, this work investigated eight types of precursors applied on flexible Mo foil substrates, some of which also contained a layer of NaF. Secondary phases, defects, and defect clusters were different in the various samples, and the surface electrical characteristics of the CZTSSe absorber layer varied accordingly. In contrast to those in the CIGS-based cells, defects and defect clusters generated in the CZTSSe absorber layer caused an upward band bending-like band structure to form at the grain boundaries (GBs), thereby forming an intra-grain (IG) current path. By improving carrier separation, a flexible CZTSSe thin-film solar cell was developed on a Mo foil substrate with a power conversion efficiency of 7.04%. Thus, the efficiency of CZTSSe thin-film solar cells could be increased through carrier separation measures that enabled the collection of holes toward the GBs and of electrons toward IGs. Graphical abstract: To realize high-efficiency CZTSSe thin-film solar cells, the current path should be formed along the intra-grains through an upward band bending-like band structure at and near the grain boundaries. fx1 Highlights: For the CZTSSe absorber layer, an upward band bending-like band structure formed at and near the GBs, and a current path formed along the IGs as holes collected toward the GBs, and electrons collected toward the IGs. Through the implementation of these carrier separation characteristics, a flexible CZTSSe thin-film solar cell on a Mo foil substrate achieved a PCE of 7.04%.